A study on the variation of zeta potential with mineral composition of rocks and types of electrolyte - Thanh, Luong Duy; Sprik, Rudolf (Vietnam Journal of Earth Sciences, 2018)
Streaming potential in rocks is the electrical potential developing when an ionic fluid flows through the pores of rocks. The zeta potential is a key parameter of streaming potential and it depends on many parameters such as the mineral composition of rocks, fluid properties, temperature etc. Therefore, the zeta potential is different for various rocks and liquids. In this work, streaming potential measurements are performed for five rock samples saturated with six different monovalent electrolytes. From streaming potential coefficients, the zeta potential is deduced. The experimental results are then explained by a theoretical model. From the model, the surface site density for different rocks and the binding constant for different cations are found and they are in good agreement with those reported in literature. The result also shows that (1) the surface site density of Bentheim sandstone mostly composed of silica is the largest of five rock samples; (2) the binding constant is almost the same for a given cation but it increases in the order KMe(Na+) < KMe(K+) < KMe(Cs+) for a given rock. References Corwin R. F., Hoovert D.B., 1979. The self-potential method in geothermal exploration. Geophysics 44, 226-245. Dove P.M., Rimstidt J.D., 1994. Silica-Water Interactions. Reviews in Mineralogy and Geochemistry 29, 259-308. Glover P.W.J., Walker E., Jackson M., 2012. Streaming-potential coefficient of reservoir rock: A theoretical model. Geophysics, 77, D17-D43. Ishido T. and Mizutani H., 1981. Experimental and theoretical basis of electrokinetic phenomena in rock-water systems and its applications to geophysics. Journal of Geophysical Research, 86, 1763-1775. Jackson M., Butler A., Vinogradov J., 2012. Measurements of spontaneous potential in chalk with application to aquifer characterization in the southern UK: Quarterly Journal of Engineering Geology & Hydrogeology, 45, 457-471. Jouniaux L. and T. Ishido, 2012. International Journal of Geophysics. Article ID 286107, 16p. Doi:10.1155/2012/286107. Kim S.S., Kim H.S., Kim S.G., Kim W.S., 2004. Effect of electrolyte additives on sol-precipitated nano silica particles. Ceramics International 30, 171-175. Kirby B.J. and Hasselbrink E.F., 2004. Zeta potential of microfluidic substrates: 1. Theory, experimental techniques, and effects on separations. Electrophoresis, 25, 187-202. Kosmulski M., and Dahlsten D., 2006. High ionic strength electrokinetics of clay minerals. Colloids and Surfaces, A: Physicocemical and Engineering Aspects, 291, 212-218. Lide D.R., 2009, Handbook of chemistry and physics, 90th edition: CRC Press. Luong Duy Thanh, 2014. Electrokinetics in porous media, Ph.D. Thesis, University of Amsterdam, the Netherlands. Luong Duy Thanh and Sprik R., 2016a. Zeta potential in porous rocks in contact with monovalent and divalent electrolyte aqueous solutions, Geophysics, 81, D303-D314. Luong Duy Thanh and Sprik R., 2016b. Permeability dependence of streaming potential coefficient in porous media. Geophysical Prospecting, 64, 714-725. Luong Duy Thanh and Sprik R., 2016c. Laboratory Measurement of Microstructure Parameters of Porous Rocks. VNU Journal of Science: Mathematics-Physics 32, 22-33. Mizutani H., Ishido T., Yokokura T., Ohnishi S., 1976. Electrokinetic phenomena associated with earthquakes. Geophysical Research Letters, 3, 365-368. Ogilvy A.A., Ayed M.A., Bogoslovsky V.A., 1969. Geophysical studies of water leakage from reservoirs. Geophysical Prospecting, 17, 36-62. Onsager L., 1931. Reciprocal relations in irreversible processes. I. Physical Review, 37, 405-426. Revil A. and Glover P.W.J., 1997. Theory of ionic-surface electrical conduction in porous media. Physical Review B, 55, 1757-1773. Scales P.J., 1990. Electrokinetics of the muscovite mica-aqueous solution interface. Langmuir, 6, 582-589. Behrens S.H. and Grier D.G., 2001. The charge of glass and silica surfaces. The Journal of Chemical Physics, 115, 6716-6721. Stern O., 1924. Zurtheorieder electrolytischendoppelschist. Z. Elektrochem, 30, 508-516. Tchistiakov A.A., 2000. Physico-chemical aspects of clay migration and injectivity decrease of geothermal clastic reservoirs: Proceedings World Geothermal Congress, 3087-3095. Wurmstich B., Morgan F.D., 1994. Modeling of streaming potential responses caused by oil well pumping. Geophysics, 59, 46-56.